Survey on energy harvesting cognitive radio network - Alfaqawi, Mohammed; Habaebi, Mohamed Hadi; Siddiqi, Mohammad Umar; Islam, Md Rafiqul; Zyoud, Al-Hareth; Al-Shibly, Mohammed Abuljawad M (Asian Research Publishing Network (ARPN), 2015)
Energy harvesting network (EHN) is a trending topic among the recent researches. This substantial attention is due to the limitations, operational cost and risks of the conventional power suppliers, such as fossil fuel and batteries. Moreover, EHN are expected to enhance energy efficiency by harvesting energy of RF and renewable sources. In contemporary research works, EHN is applied to CR technology. This energy harvesting cognitive radio network (EHCRN) is expected to utilize both energy and electromagnetic spectrum efficiently. However, EH-CRN is facing enormous challenges related to technical design. Some of these challenges are reviewed in recent surveys. However, other challenges such as optimizing the network throughput and EH-CRN implementation models were not the focus of these researches. Therefore, the aim of this survey is to review EH-CRN research works by focusing the survey perspective on maximizing the network throughput and the implementation models.